Comparison of paternal and maternal feeding practices and parenting styles between healthy weight and overweight or obese primary school children - Leiu, Kok Hong; Chin, Yit Siew (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Parents play significant roles in developing the behaviour of their children towards food. However, mothers usually represent the parents of the children in previous studies, while fathers were left out and their contribution remained unknown. This study compared paternal and maternal feeding practices and parenting styles between overweight or obese (OW/OB) and normal weight (NW) primary school children. Methods: There were 419 children aged 10 to 11 from four randomly selected national primary schools being screened for their body weight and height. There were 105 children identified as OW/OB and matched with 105 NW children based on sex, age and ethnicity, whose both their parents were then recruited as study subjects. Parents reported their personal body weight and height, and completed a questionnaire on parenting styles and feeding practices. Results: There were 34.9% of children overweight and obese, and more than half of their fathers (66.5%) and mothers (52.5%) were over-weight and obese. Both fathers and mothers of the OW/OB children perceived their children to be slightly heavier, but a majority of them perceived their children’s body weight status less accurately and applied less pressure to eat. Fathers of the OW/OB children were more in the obese category, performed indulgent parenting style, perceived less feeding responsibility and applied less monitoring on their children, but not mothers. Conclusion: There were distinct differences in paternal and maternal feeding practices and parenting styles between OW/OB and NW children. Researchers should encourage fathers to involve in childhood obesity research instead of focusing on mothers.